Multiply 9 + -6i and 2 + -4i

a = bi = <-- Enter a and bi piece
c = di = <-- Enter c and di piece (not needed for square root or absolute value or conjugate)

Perform the complex number multiplication: (9 - 6i)(2 - 4i)

The formula for this using the FOIL method is: (a * c) + (b * c) + (a * d) + (b * d) where:
a = 9, b = -6, c = 2, and d = -4

Now plug these values into our formula and evaluate:
(9 - 6i)(2 - 4i) = (9 * 2) + (-6i * 2) + (9 * -4i) + (-6i * -4i)
(9 - 6i)(2 - 4i) = 18 - 12i - 36i + 24i2

Group the like terms that contain i:
(9 - 6i)(2 - 4i) = 18 + (-12 - 36)i + 24i2
(9 - 6i)(2 - 4i) = 18 - 48i + 24i2

Simplify our last term:
i2 = √-1 * √-1 = -1, so our last term becomes:
(9 - 6i)(2 - 4i) = 18 - 48i + 24* (-1)
(9 - 6i)(2 - 4i) = 18 - 48i - 24

Now group the 2 constants and finalize our answer
(9 - 6i)(2 - 4i) = (18 - 24) - 48i
(9 - 6i)(2 - 4i) = -6 - 48i